Student Consumerism in the Digital Era: A Comparative Study of Socialist Economics and Islamic Economics - Supandi, Muhammad Diaz; Rahmat, Andra Dwi; Fahmi, Moh. Ulwanul Roid Al; Mahmudi, Fauzan (Indonesian Journal of Islamic Business and Economics (IJIBE), 2026)
This study addresses the significant academic gap in critically examining the pervasive phenomenon of student consumerism in the digital era through the lens of alternative economic systems. While existing research often analyzes this behavior via psychological or sociological approaches, a systemic critique from paradigms fundamentally opposed to market capitalism is scarce. This research aims to fill this void by conducting a comparative analysis of how Socialist Economics and Islamic Economics diagnose, critique, and offer alternatives to the hyper-consumptive behaviors of students embedded in digital platforms. The urgency of this inquiry is multidimensional, extending from the practical need to foster critical economic literacy among students to the academic imperative of dialoguing between two major alternative economic traditions, all within the global context of ecological and social crises fueled by unsustainable consumption. Employing a qualitative, library research methodology with a critical-comparative framework, this study systematically deconstructs the digital marketplace's phenomenology before applying core concepts from each paradigm—such as alienation and commodity fetishism (Socialist) versus maslahah, israf, and amanah (Islamic). Its novelty lies in its rare comparative focus, its translation of abstract principles into tools for analyzing concrete consumption acts, and its reconceptualization of students as both objects of systemic forces and potential agents of change. The analysis ultimately reveals a profound convergence in both paradigms' condemnation of consumerism's dehumanizing effects, yet a fundamental divergence in their ontological roots, causal explanations, and envisioned solutions, highlighting the possibility for strategic complementarity in forging a critique of contemporary digital capitalism.